2014
DOI: 10.1097/med.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of endocrine comorbidities in patients with cystic fibrosis

Abstract: Purpose of review The aim of this review is to provide an update on various relevant endocrine aspects of care in adolescents and adults with cystic fibrosis (CF). Recent findings As life expectancy in CF has continuously improved, endocrine complications have become more apparent. The common endocrine complications include cystic fibrosis related diabetes (CFRD), cystic fibrosis related bone disease, vitamin D deficiency and poor growth and pubertal development. Thyroid and adrenal disorders have also been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 105 publications
(147 reference statements)
0
24
0
12
Order By: Relevance
“…13 Because the median age of survival in patients with CF is now closer to 40 years, 13,14 there has been an increase in prevalence of multiple comorbidities, including CF-related bone disease (CFBD). Known risk factors for CFBD include poor nutrition, chronic lung infection and inflammation, pancreatic insufficiency, delayed puberty, decreased physical activity, and medications, including glucocorticoids and transplant-related therapies.…”
Section: Pediatric Bone Health: Cystic Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…13 Because the median age of survival in patients with CF is now closer to 40 years, 13,14 there has been an increase in prevalence of multiple comorbidities, including CF-related bone disease (CFBD). Known risk factors for CFBD include poor nutrition, chronic lung infection and inflammation, pancreatic insufficiency, delayed puberty, decreased physical activity, and medications, including glucocorticoids and transplant-related therapies.…”
Section: Pediatric Bone Health: Cystic Fibrosismentioning
confidence: 99%
“…Known risk factors for CFBD include poor nutrition, chronic lung infection and inflammation, pancreatic insufficiency, delayed puberty, decreased physical activity, and medications, including glucocorticoids and transplant-related therapies. 15,16 The presence of impaired glucose metabolism in CF-related diabetes and possible direct effect of the CFTR on osteoclast activation 12,13 may also be responsible for the bone disease reported in both children and adults.…”
Section: Pediatric Bone Health: Cystic Fibrosismentioning
confidence: 99%
“…In the pancreas of patients with CF, stasis of mucous, reduction of pancreatic fluid flow and increased concentration of protein results in pancreatic fibrosis, destruction and eventual insufficiency, leading to malabsorption of fat and fat-soluble vitamins, including vitamin D(5, 6). Other endocrine abnormalities can occur in patients with CF(7). Cystic fibrosis related diabetes (CFRD), delayed puberty and impaired fertility are also commonly occurring endocrine co-morbidities in patients with CF(7).…”
Section: Introductionmentioning
confidence: 99%
“…Other endocrine abnormalities can occur in patients with CF(7). Cystic fibrosis related diabetes (CFRD), delayed puberty and impaired fertility are also commonly occurring endocrine co-morbidities in patients with CF(7). …”
Section: Introductionmentioning
confidence: 99%
“…With iodine-containing expectorant no longer in routine use, the prevalence of thyroid dysfunction in CF patients is now unknown (11). A recent small study by Volta et al showed that there was no significant thyroid dysfunction observed in 17 CF patients compared to controls, and concluded that this may be related to improved nutritional status and lack of iodinecontaining medication use (12).…”
Section: Introductionmentioning
confidence: 99%